Freshwater Fishing from a Sea-Coast Settlement: the Ertebølle locus classicus Revisited - Bødker, Inge (Journal of Danish Archaeology, 1986)
Freshwater Fishing from a Sea-Coast Settlement - the Ertebølle locus classicus Revisited